Deep Learning to Aid Prescription Processing & Inventory Management for Local Pharmacies through Smartphone Application - Hasib Ullah Hasib; Mohammad Ahsan Chowdhury (International Journal of Supply Chain Management, 2021)
One of the most common types of medical errors is medication errors and also considered one of the most preventable errors. Most of the prescriptions that are provided by doctors are still handwritten. Mistakes can occur very easily in handwritten prescriptions as well as the possibility of the pharmacist finding the handwriting illegible which can lead to the consumption of incorrect drugs and doses in patients. Usage of digital prescriptions or also known as e-prescription can reduce medication errors dramatically. First of all, it omits the possibility of illegible handwriting. Thus, the pharmacists can provide the correct medicine and doses to the patients.This study is conducted to show how Deep Learning can hugely contribute to providing a solution for medication errors and how it can create a marketplace for pharmacies that uses this advanced technology that directly connects the local pharmacy stores, diagnostic centers, and hospitals to fulfill patient’s extensive medical needs.